Queer theology: beyond apologetics - Tonstad, Linn Marie (Cascade companions, 2018)
What do Christianity and queerness have to do with each other? Can Christianity be queered? Queer Theology offers a readable introduction to a difficult debate. Summarizing the various apologetic arguments for the inclusion of queer people in Christianity, Tonstad moves beyond inclusion to argue for a queer theology that builds on the interconnection of theology with sex and money. Thoroughly grounded in queer theory as well as in Christian theology, Queer Theology grapples with the fundamental challenges of the body, sex, and death, as these are where queerness and Christianity find (and, maybe, lose) each other